Braiding A/r/tography & Métissage: Thinking together on the work of Sonny Assu - Rallis, Nicole; Leddy, Shannon; Irwin, Rita L. (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2024)
Three art educators come together to respond to the work of Sonny Assu, Ligwilda’xw of the Kwakwaka’wakw Nations, who was invited as an artist-in-residence to a graduate seminar on Indigenous visual expression as pedagogy. Engaging with the concepts of Indigenous métissage, diffraction, and a/r/tography, we weave together our personal stories, identities, and practices. We discuss ways to engage in anti-colonial teaching practices that provide openings for students to retrace, reimagine, and reconcile their understandings of Indigenous-settler relations in Canada. Our call to action asks art educators to consider Indigenous métissage as an important diffractive research practice and pedagogical praxis.